PEMBINAAN DALAM MENGENALI DAN MENYELESAIKAN SOAL-SOAL OLIMPIADE MATEMATIKA TINGKAT NASIONAL DI SMA IT AL-KAMAL NW NARMADA - Neny Endriana; Nila Hayati; Syarifuddin Syarifuddin (Taroa: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this service is to improve the abilities and skulls of the coach teacher in analyzing and solving math Olympiad questions, the Olympiad coach teacher can transfer this knowledge to students and orther teacher friends in their respective school environments. To prepare superior and outstanding student nasional Olympiads. The coaching methods is carried out by brainstorming methods (opinions sharing), Lecture methods, problem solving simulation methods (problem solving), and discussion methods. The expected results are that the participants take part in coaching and the Head of SMA IT Al-Kamal Narmada and the team implementing the Olympic activites hope that the lecturers, especially from Hamzanwadi Selong University and Muhammadiyah Bima University, are willing to provide intensive coaching to the participants. Satisfactory improvement can also be seen from the presentasion of material and discussion of Olympic questions which were well digested by the participants.